ChemInform Abstract: Supported Gold Nanoparticles as Efficient and Reusable Heterogeneous Catalyst for Cycloisomerization Reactions. Issue 42 (October 2015) - Schroeder, Felix; Ojeda, Manuel; Erdmann, Nico; Jacobs, Jeroen; Luque, Rafael; Noel, Timothy; Van Meervelt, Luc; Van der Eycken, Johan; Van der Eycken, Erik V.
Abstract The novel catalyst system contains gold nanoparticles supported on Al‐SBA15 prepared by the ball‐milling process.